Propensity for Credit Usage in Brazil (2012-2023): Empirical aspects of intertemporal choice - Gomes, Raquel (2024)
The present article focuses on the use of credit by Brazilian households. Its objective was to identify the efects of theoretical factors from the intertemporal choice model related to credit usage in Brazil. The theoretical model addressed was the intertemporal choice model from a microeconomic perspective, along with its implications in the Permanent Income Hypothesis and the Life Cycle Hypothesis. The study utilizes data from the Time Series Manager System of the Central Bank of Brazil, encompassing income, expectations, savings, interest rates, inflation, indebtedness, and default, employing VAR-VEC econometric modeling. The main results indicate that savings formation aligns with the analyzed theoretical model, while indebtedness exhibited expected behavior concerning expectations, inflation, and default, a variable added based on the literature review.